Use of vaginal cytology in the detection of the estral cycle phase of bitches and its relation with age and body condition score, Belém, Pará (Research, Society and Development, 2021)
Vaginal cytology allows the detection of the estrous cycle phase and reproductive disorders in bitches. The objective of the study was to perform the use of vaginal cytology to detect the estrous cycle phase in female dogs (Canis lupus familiaris) in the city of Belém, Pará State, Brazil. The vaginal cytological exams were previously authorized by the guardians, being carried out in 23 female dogs, without defined breed (SRD), with age between 6 months and 14 years, weighting from 5 to 25 kg, before being submitted to ovariosalpingohysterectomy (OSH). The results showed that 13.04% (3/23) of the females were in proestrus; 21.73% (5/23) in estrus; 39.13% (9/23) in diestrus and 26.08% (6/23) in anestrus. Thus, it was demonstrated that vaginal cytology can be used in the clinical routine of canine females for diagnosis of the estrous cycle phase, emphasizing that the association with clinical and hormonal evaluation favors greater accuracy in this diagnosis.